European Territorial Cooperation and European Integration - Medeiros, E. (Territorial and Inter-organizational Cooperation, 2020)
- First of all, I would like to thank the organisation (and especially Prof. Joanna Kurowska) for the honourable invitation to speak as a keynote speaker in this very interesting and relevant event. - Indeed, in pandemic times, which have affected in particular cross-border processes and flows, such events allow us to discuss and debate relevant related to the process of European Territorial Cooperation, which can be generically understood as a process of reducing systematic reduction of all sorts of persisting border barriers. - In this context, I will start my presentation by invoking the title of the latest book from Andreas Faludi, which is self-explanatory: ‘The Poverty of Territorialism’. Territorialism is, in a generic sense, the paradigm we are living for the past couple of centuries in which the world is divided into different nation-states or countries. - For Faludi, provokes a series of territorial development bottlenecks, since it undermines territorial functional relations, more sustainable territorial coalitions, and the implementation of certain spatial planning processes, and hinders several aspects of daily and national life that are beyond a government’s control. - In this sense we have been advocating, for a long time, the implementation of a one world, one system paradigm, or a global deterritorialism governance paradigm as a concrete policy action to reduce the negative effects posed by the presence of national boundaries. - It was with some interest that we listen to the State of the Union speech from the President of the European Commission: Ursula von der Leyen … and I have to say that I subscribe most of the presented strategy. However, I would that she would bring forward specific measures that could avoid the problems posed by the ‘covidfencing’, that is the closing of the national boundaries due to the spreading of the COVID-19. - As many sources have pointed out, many of these measures have led to local-regional population and entities protests, since covidfencing has undermined the normal functioning of cross-border commuting in several cross-border passages, and the economy of cross-border areas. - But also at the national level, the poverty of territorialism was visible in the need that some countries have for cross-border workers to maintain their public services (namely hospitals). As examples, Luxembourg needed to keep its borders open form cross-border medical workers coming from France. There was even the proposal to keep them slepping in Luxembourg under certain payment conditions. The same happened for Switzerland and Austria which needs cross-border medical workers from eastern European countries. - So, it was with satisfaction that I saw the creation of the cross-border alliance by MOT+AEBR+CESCI, which realised that similar future pandemic scenarios require a different approach. There is a need to contain the spread of pandemics at their source. This does not necessarily imply the shutdown of national borders. - So, in my view, the EU should support a one Europe, one System approach of deterritorialism. It is true that in the economy policy arena we have the example of the Euro. But we all know that, as it stands, this coin beneficiates a few countries like Germany and Holland. For it to function to the benefit of all Eurozone there is a need to have a common fiscal system and, I would argue, a similar salary system. I see no reasons that my salary is not similar my colleagues in Germany or Denmanrk. And that the minimum wage which the President of the EC defends should provide dignity to the worker, should also have the same value within the EU. As president Obama stated, the one that works cannot be poor. - Alongside, as following from the recent work of the EC on the persistent border barriers in Europe, it is known that the most relevant for Europeans are of Administrative-Legal character. These include barriers related with the presence of difference social security systems and diploma recognition. In addition, language continues to be regarded as one of the three main cross-border barriers encountered by Europeans. In this regard, there is a need to provide key information for cross-border workers in a common language, that is English, which is widely accepted as the universal language. - Furthermore, there a lot a work to be done to normalise cross-border transport systems, information, ticketing, scheduling, etc. along with the improvement of its capacity in view of the current needs of the more that 2M European cross-border commuters, 400.000 of which cross French borders - As we know, the concept of European Integration encompasses several analytic dimensions: institutional, cultural, economic, social, etc. Instead, the notion of European Territorial Cooperation is specifically associated with the goal of reducing border barriers. Hence, its has a close connotation with the notion of Cross-Border Cooperation, which ultimately should be, in by view, a policy goal aiming to reducing border barriers. - In this regard, and following from my own studies: My PhD compared two Interreg-A programmes (Portugal-Spain and Sweden-Norway) and their contribution to reducing border barriers. For instance, the first three PT-SP Interreg-a programmes dedicated 70% of their funding to support the construction of physical accessibilities. These included the still most financed and iconic Interreg-a projects: the Guadiana bridge which links Algarve and Andalucía, still the only cross-border road linking these regions, as far as I know. - As stated, the three most persisting border barriers in Europe are respectively the ones related with Legal-Administrative issues, the language and the lack or difficult physical accessibility. I am aware that the Interreg-a programme cannot, by itself, solve many of these CB barriers, and namely the legal-administrative ones, since they require national administration interventions. - But the covidfencing can be used to identify certain areas of policy intervention which can help to mitigate these border barriers, as is the case of the problems encountered in the functioning of public services such as Hospitals, cross-border transports, which were largely stopped or placed a minimum service. There were also several situations which affected the normal functioning of cross-border commuting, in particular in Eastern-European borders. - The following maps finalise my presentation, by showing the EU Interreg-a areas which could beneficiate more from the EU investments in reducing five types of border barriers. - Starting with accessibility related barriers, we used our own data, collected in 2017 on the presence and capacity of CB public transports in Europe (Bus and Trains). This shows darker areas which require higher volumes of public investment in improving CB public transports. Just to note, I received a valid comment from Jean Peyrony, telling me that last year the border between France and Switzerland in the Geneve area, received a new CB train, which helped to mitigate the CB transport problem in the area. But to be comparable, I need to maintain the current data. - At the institutional level, it is known that time is key to consolidate CB institutional formal arrangements, and that the NWE together with the Nordic countries have been cooperation in a formal manner since the mid-1950s. So the remaking CB areas of Europe need to catch-up in this domain, despite the many positive advances made with the implementation of EGCTs for I - As regards Economic cooperation, we used data from our Polytechnic Milano colleagues which show that CB areas where there is a higher economic capital potential to explore: NWE - In the social cooperation, a recent study from ESPON identified many existing cases of CB public services, which need to be further explored in basically all EU CB areas, to increase the level of social cooperation - Finally, the cultural domain is supported by data collected for an EC report in which I acted as an adviser, and that identified several Eastern European CB areas (as well as some in Scandinavia and the Iberian Peninsula) still requiring the mitigation of substantial cultural barriers.